P821 Sexual behavior in adolescents before and after introduction of the HPV vaccination in canada. (14th July 2019) - Ogilvie, Gina; Donken, Robine; Pedersen, Heather; Bettinger, Julie; Goldman, Ran; Saewyc, Elizabeth; Dobson, Simon; Naus, Monika; Sadarangani, Manish
Abstract : Background: Currently all Canadian jurisdictions have implemented school-based human papillomavirus (HPV) vaccination into their routine immunization programs. Uptake rates in girls vary from 52.6% to 89.3% between jurisdictions. At the time of implementation, there were concerns that HPV vaccination could lead to riskier sexual health choices among adolescents. This systematic review explores the influence HPV vaccination programs on sexual behavior among adolescent girls in Canada. Methods: A systematic literature review was performed using PubMed, followed by a cited reference search. Studies were included if they reported sexual behaviors or biological outcomes in Canadian participants. We descriptively compared sexual behavior and rates of pregnancy and sexually transmittable infections (STI) in the pre- and post vaccination era or amongst vaccinated and unvaccinated. Results: In total, 38 Canadian articles were identified and four met eligibility criteria. HPV vaccination was not associated with a diagnosis of STI (OR 0.81, 95%CI 0.63–1.04 and 0.91, 95%CI 0.78–1.06, respectively). Being eligible for HPV vaccination was not associated with pregnancy (OR 0.69, 95%CI 0.49–0.98 and OR 1.01, 95%CI 0.93–1.10). One study found that girls eligible for HPV vaccination were less likely to ever have had sexual intercourse (OR 0.89, 95%CI 0.82–0.98). HPV vaccination was not associated with the lifetime number of partners for vaginal or receptive anal intercourse. There was no difference in having had ≥3 sexual partners within the past year. Only the lifetime number of partners for oral receptive intercourse was found to be higher among vaccinated (mean 2.50) than unvaccinated (mean 1.51) women. Use of condoms at last intercourse was slightly higher in vaccine eligible cohorts (OR 1.28, 95%CI 1.10–1.49). Conclusion: HPV vaccination has not been associated with riskier sexual behavior, increased STI or pregnancy rates among young Canadian adolescents. These findings are in line with those from an increasing number of international studies. Disclosure: No significant relationships.